Epidemiology of Antiretroviral Therapy Related Adverse Drug Reactions and its Predictors Among Patients with Human Immunodeficiency Virus/AIDS in Ethiopia: A Systematic Review and Meta-analysis - Woretaw S Zewdu MSc; Samuel B Dagnew MSc; Mulugeta M Zeleke MSc; Yared A Ferede MSc; Achenef B Kassie MSc; Tilay A Moges MSc; Muluken A Alemu MSc (Journal of the International Association of Providers of AIDS Care, 2025)
Objective Adverse drug reactions (ADRs) induce iatrogenic harm in antiretroviral therapy (ART) care continuum. However, there is a dearth of concrete evidence in a resource-limited setting. Thus, this study was designed to consolidate existing knowledge, thereby informing policy and clinical care to improve patient safety. Design Systematic review and meta-analysis. Data sources PubMed, CINAHL, Web of Science, and EMBASE databases were searched. Eligibility criteria Employing the condition, context, and population framework, observational primary studies were included. Data extraction and synthesis Independent reviewers undertook data extraction and synthesis. This meta-analysis employed the random-effects restricted maximum likelihood (REML) method, with its protocol preregistered on the International Register of Systematic Reviews (CRD42024546390). Results The pooled prevalence of ADRs was 36.7% [95% CI: 26.6-46.9, I 2  = 99.64%]. Conclusion Altogether, this study revealed that ART-related ADRs in Ethiopia was 36.7%, underscoring rigorous monitoring. Giving special emphasis to patients with female gender, advanced disease, comorbidities, malnutrition, TB treatment, and poor adherence is a prudent decision.